2022
DOI: 10.1002/adem.202201392
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytical and Photothermal Behavior Derived from Self‐Assembly Microsuperlattices of Cu1.8S for Laser Ignition

Abstract: Laser ignition is considered to be a novel ignition technique with high safety and reliability. With the aim of widening the range of industrial and scientific applications for laser ignition, it is extremely desirable to increase the laser sensitivity of energetic materials because most of them are laser insensitivity and unignitable with diode laser. Herein, a facile strategy is presented to prepare ammonium perchlorate (AP) coated with Cu1.8S microsuperlattices via a self‐assembly process. The resulting AP@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For a long time, however, most energetic materials have been tolerating laser insensitivity and are hard to be ignited upon an NIR laser stimulation, , hindering the development of laser initiation/ignition in aero and military areas. Recently, it was reported that photothermal conversion materials have increased the laser sensitivity of energetic materials through doping or coating. An innovative promising explosive, dihydroxylammonium 5,5′-bistetrazole-1,1′-diolate (TKX-50), draw increasing attention because of its high energy and insensitivity, which is desired for the safety of weapons and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, however, most energetic materials have been tolerating laser insensitivity and are hard to be ignited upon an NIR laser stimulation, , hindering the development of laser initiation/ignition in aero and military areas. Recently, it was reported that photothermal conversion materials have increased the laser sensitivity of energetic materials through doping or coating. An innovative promising explosive, dihydroxylammonium 5,5′-bistetrazole-1,1′-diolate (TKX-50), draw increasing attention because of its high energy and insensitivity, which is desired for the safety of weapons and equipment.…”
Section: Introductionmentioning
confidence: 99%